first subtract 2x from both sides to get:
-7=3x+7
then add 7 to both sides to get:
-14=3x
x=-14/3 or -4 2/3
2006-11-02 10:26:48
·
answer #1
·
answered by Anonymous
·
3⤊
0⤋
2x - 7 = 5x + 7
2x - 7 - 2x = 5x + 7 - 2x
-7 = 3x + 7
-7 + 7 = 3x + 7 - 7
0 = 3x
0/3 = 3x/3
0 =x
that makes this answer not true because 2(0) -7 =5(0) +7 is
- 7 = +7
2006-11-02 10:33:39
·
answer #2
·
answered by Anonymous
·
0⤊
1⤋
2x - 7 = 5x + 7
-7 -7 = 5x - 2x
-14 = 3x
-14 / 3 = x
2006-11-02 10:31:09
·
answer #3
·
answered by Anonymous
·
1⤊
0⤋
2x - 7 = 5x + 7
(2x - 5x) = 7 + 7 (combine like terms)
-3x = 14 (divide by 3)
x = -14/3
2006-11-02 10:30:11
·
answer #4
·
answered by Mark D 1
·
2⤊
0⤋
2x - 7 = 5x + 7
-5x +7
-3x = 14
x = - 14/3
2006-11-02 11:27:24
·
answer #5
·
answered by sweetchik5188 2
·
1⤊
0⤋
2x-7=5x+7
-2x -2x
-7=3x+7
-7 -7
-14=3x
/3 /3
4-2/3=x
2006-11-02 11:10:26
·
answer #6
·
answered by Anonymous
·
0⤊
1⤋
you should do 2x+7=5x+13 -2x =-2x ---------------- 7=3x+13<-----the reason i subtracted 13 from both part is because i already took -13 =-13 2 from the different part... so this suggests that is necessary to take -------------- from the option part -6=3x 3 =3 ---------- <----------i divided 3 from both part...then my answer got here out to be -3 -3=x
2016-12-05 11:43:50
·
answer #7
·
answered by ? 4
·
0⤊
0⤋
-14=3 x or -4and2/3=x
2006-11-02 10:30:58
·
answer #8
·
answered by red sox! 3
·
0⤊
1⤋
-4.2=x
2006-11-02 10:32:22
·
answer #9
·
answered by Anonymous
·
0⤊
1⤋